Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Mobil Xpander (PT. Sardana Indah Berlian Motor) - Sugito Sugito (Universitas 17 Agustus 1945 Semarang, 2023)
The purchase decision is the stage in the buyer's decision-making process where the consumer actually buys. Decision-making actions that include decisions about the types and benefits of products, decisions about product forms, decisions about brands, decisions about the number of products, decisions about the seller and decisions about when to buy and how to pay. The purpose of this study is to analyze the simultaneous and partial effect of product quality and service quality on purchasing decisions. The benefits of this research are for writers as an addition to knowledge about the effect of product quality and service quality on purchasing decisions, for companies as information and guides for companies to improve purchasing decisions through product quality and service quality in the future, and for other parties as input and reference for researchers furthermore. The hypothesis in this research is that there is a positive and significant effect both simultaneously and partially on product quality and service quality on the decision to buy an Xpander car. In this study using a quantitative/associative approach and sampling techniques using non-probability sampling as many as 96 respondents taken from consumers of PT. Sardana Indah Berlian Motor. Sources of data in this study are from primary data and secondary data. Data collection techniques in this study used questionnaires and documentation. The data obtained were then processed and analyzed using multiple linear regression analysis technique models, and processed with the help of the SPSS program through validity tests, reliability tests, data normality tests, multicollinearity tests, heteroscedasticity tests, simultaneous effect tests, partial effect tests, and the coefficient of determination. The results of testing the hypothesis indicate that product quality and service quality simultaneously and partially significantly influence purchasing decisions. Product quality is the dominant variable influencing purchasing decisions.